L’approche communicative dans l’enseignement des langues quels impacts sur les apprenants du FLE au Ghana - Kaiza, E.K. (My University, 2020)
This article seeks to shed light on the communicative approach to language teaching and also to examine the impact of such an approach on French learners in three Municipalities in the Volta Region of Ghana. If communicative approach is aimed at developing learners’ oral skills, the performance of learners who were taught through this approach leaves much to be desired during the French Orals Exams from 2010 to 2014. The article therefore seeks to assess the communicative competence of French learners in classroom practices, the difficulties that confront both teachers and learners of French as a Foreign Language using the communicative approach in an Anglophone system. It seeks also to outline the impact of this approach on French learners in the Senior High schools in Volta Region. Through questionnaire based on K. Orecchioni’s conversational theory (1990), the research conducted among 30 teachers reveals that the poor communicative competence observed among French learners is, on the one hand, due to the non-effective application of the communicative approach in class and, on the other hand, due to lack of motivation on the part of learners. Strategies were therefore proposed to improve the communicative approach to Teaching and learning French as a Foreign Language in an Anglophone environment.
Research Article
Keywords: Approach; Communication; competence; impact; learning